2017
DOI: 10.1039/c7fo00393e
|View full text |Cite
|
Sign up to set email alerts
|

A study of the prebiotic-like effects of tomato juice consumption in rats with diet-induced non-alcoholic fatty liver disease (NAFLD)

Abstract: Gut microbiota may play a role in the pathogenesis of NAFLD. We investigated whether tomato juice consumption for 5 weeks could ameliorate high-fat diet-induced alterations in certain intestinal bacterial groups and products arising from their metabolism (short-chain fatty acids and microbial phenolic catabolites). For this, we used a rat model with NAFLD induced by a high-fat diet, involving four experimental groups: NA (standard diet and water), NL (standard diet and tomato juice), HA (high-fat diet and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…reported that the gut of HFD‐induced non‐alcoholic fatty liver disease rats exhibited a decreased abundance of Lactobacillus . [ 65 ] In this study, the supplementation of LCP or Vc significantly increased the abundance of these probiotics, which alleviats the OSD of the intestinal tract. Recently, several studies have reported that Akkermansia ( Akk .)…”
Section: Discussionmentioning
confidence: 74%
“…reported that the gut of HFD‐induced non‐alcoholic fatty liver disease rats exhibited a decreased abundance of Lactobacillus . [ 65 ] In this study, the supplementation of LCP or Vc significantly increased the abundance of these probiotics, which alleviats the OSD of the intestinal tract. Recently, several studies have reported that Akkermansia ( Akk .)…”
Section: Discussionmentioning
confidence: 74%
“…The ability of other antioxidant-rich nutrients to increase plasma TAC and hence decrease risks of NAFLD through modifications of oxidative stress has been well documented. These nutrients include bayberry juice (33) , chocolate (34) , onion (35) , lettuce (36) and tomato products (37) . Findings have been verified even in supplementary interventions with antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…[113,114] Similarly, another study demonstrated that tomato juice ameliorates dietinduced liver dysfunction by regulating the content and structure of the gut microbiota. [115] NAFLD is always accompanied by a reduction in the abundance of beneficial intestinal bacteria, such as Bifidobacterium and Lactobacillus, and tomato juice reverses this change and might be a potential nutritional supplement to treat NAFLD. In several animal and clinical trials, vitamins D and E also showed potential effects on NAFLD/NASH prevention and therapy.…”
Section: Micronutrient Antioxidantsmentioning
confidence: 99%